2014
DOI: 10.18632/aging.100677
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiling of the microRNA-mRNA regulatory network in skeletal muscle with aging

Abstract: Skeletal muscle degenerates progressively, losing mass (sarcopenia) over time, which leads to reduced physical ability and often results in secondary diseases such as diabetes and obesity. The regulation of gene expression by microRNAs is a key event in muscle development and disease. To understand genome-wide changes in microRNAs and mRNAs during muscle aging, we sequenced microRNAs and mRNAs from mouse gastrocnemius muscles at two different ages (6 and 24 months). Thirty-four microRNAs (15 up-regulated and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 44 publications
(56 reference statements)
10
89
0
Order By: Relevance
“…Changes in miRNA expression in muscle with age have been described in rodents and humans (Drummond et al ., 2008; Kim et al ., 2014); however, the functional relevance of this is not yet understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in miRNA expression in muscle with age have been described in rodents and humans (Drummond et al ., 2008; Kim et al ., 2014); however, the functional relevance of this is not yet understood.…”
Section: Discussionmentioning
confidence: 99%
“…Satellite cell‐specific Dicer knockout in a mouse model resulted in mild myofibre atrophy (Cheung et al ., 2012). Although differential expression of miRs in muscle has been described during aging (Drummond et al ., 2008; Kim et al ., 2014), the relevance of these changes is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A), 47 miRNAs were significantly up-regulated, and 71 miRNAs were down-regulated in old myoblasts (Tables 1, 2). We recently reported that 57% of miRNAs down-regulated in old muscle tissues were located in the Dlk-Dio3 region of chromosome 12 (Kim et al 2014). Interestingly, 63 of the 71 miRNAs (89%) down-regulated in old myoblasts were also located in the Dlk-Dio3 genomic region, suggesting that miRNAs expressed from this locus may be relevant to the process of muscle aging.…”
Section: Differential Expression Of Mirnas Between Young and Old Myobmentioning
confidence: 98%
“…The finding that skeletal muscle-specific knockout of Dicer, a key enzyme for maturation of precursor miRNAs (pre-miRNA), causes a decrease in muscle mass and abnormal muscle formation in mice, causing perinatal death, suggests that miRNAs have a key role in normal muscle development (O'Rourke et al 2007). In addition, we recently found that the miRNA-mRNA regulatory network in skeletal muscle changes with age, suggesting that miRNAs may be involved in the process of muscle aging (Kim et al 2014).…”
mentioning
confidence: 99%